Is Kuala Lumpur Stock Exchange an Emerging Market? - Narayanan, Subramani (1997)
Malaysian KLSE had achieved a tremendous growth and depth in the market in the past ten years. Should KLSE still be considered as an emerging market although the characteristics ofKLSE are pointing more towards a matured market? KLSE has been classified, as an emerging market just because of Malaysia's per capita income is less than US$ 7911? It is because International Finance Corporation (IFC) had defined and linked financial market development to economic development policy based on income per capita. IFe's classification is useful only of pursuing economic development policy formulation. Emerging Stock markets had grown so rapidly than the developed markets that very little distinction could be made between developed and emerging markets. The reasons for rapid growth include better quality of life of the people of the developing world, faster national economic growth, improved stock market infrastructure, more disposable income to invest on the part of the citizens within the emerging markets, better investment returns, increasing listing of companies. All these factors are moving together towards a dynamic and vibrant stock market that pushed up the volume and the market capitalization of the stock market. Technical enhancements too contributed towards the growth of stock markets especially in the field efficient regulatory procedures such as central registry, speedy clearing, transparency of trading and information and other protective measures have also enhanced growth of stock markets in the emerging countries.Therefore, Malaysian stock market which has a favorable investment climate and political stability should be considered as newly developed stock market based on high level of openness and relatively transparent, well established regulatory procedures and good judicious legal system that is acceptable by international standards.